Respuesta :

Answer:


hope this helps lol

Ver imagen MarcuSiuuu

Answer:

[tex](4a)^2(-a^2 b)^3 +5a^8 b^3[/tex]

Apply exponent rule  [tex](a \cdot b)^c=a^cb^c[/tex]

[tex](4a)^2=4^2 \cdot a^2=16a^2[/tex]

[tex](-a^2b)^3=(-a^6b^3)[/tex]

[tex]\implies (16a^2)(-a^6b^3)+5a^8b^3[/tex]

[tex]\implies -16a^2a^6b^3+5a^8b^3[/tex]

Apply exponent rule  [tex]a^b \cdot a^c=a^{(b+c)}[/tex]

[tex]a^2a^6=a^{(2+6)}=a^8[/tex]

[tex]\implies -16a^8b^3+5a^8b^3[/tex]

Add similar elements:

[tex]\implies -11a^8b^3[/tex]